Quantitative Traits of Muscovy Duck (Cairina moschata) in Ciayumajakuning, West Java, Indonesia - widianingrum, Dini; Widjastuti, Tuti; Anang, Asep; Setiawan, Iwan (Universitas Halu Oleo, 2023)
Biological characteristics covering qualitative and quantitative traits are essential to study phenotypic characteristics in livestock farming. This research investigates the quantitative attributes of Muscovy duck in Ciayumajakuning (Cirebon, Indramayu, Majalengka, and Kuningan Regency), West Java, Indonesia. Observations were conducted on 673 Muscovy ducks aged six months using a survey method with a sample selection of multistage probability stratified random sampling. Data analysis uses univariate and multivariate discriminant analysis. The quantitative data shows that the body size of a drake is more significant than the duck. Drake from Cirebon has a close kinship with Drake from Majalengka and Kuningan, but they have a distant relationship with Indramayu Muscovy ducks. Duck from Cirebon has a close kinship with ducks from Indramayu and Majalengka, but they have a distant relationship with ducks from Kuningan. It is concluded that the quantitative traits of the Muscovy duck in Ciayumajakuning are diverse. Keywords: Quantitative Traits, Muscovy duck, Ciayumajakuning